Discovery of a potent and selective Axl inhibitor in preclinical model. (1st June 2021) - Inoue, Satoshi; Yamane, Yoshinobu; Tsukamoto, Shuntaro; Azuma, Hiroshi; Nagao, Satoshi; Murai, Norio; Nishibata, Kyoko; Fukushima, Sayo; Ichikawa, Kenji; Nakagawa, Takayuki; Hata Sugi, Naoko; Ito, Daisuke; et al.
Graphical abstract: Abstract: Axl and Mer are a members of the TAM (Tyro3-Axl-Mer) family of receptor tyrosine kinases, which, when activated, can promote tumor cell survival, proliferation, migration, invasion, angiogenesis, and tumor-host interactions. Chronic inhibition of Mer leads to retinal toxicity in mice. Therefore, successful development of an Axl targeting agent requires ensuring that it is safe for prolonged treatment. Here, to clarify whether enzyme inhibition of Mer by a small molecule leads to retinal toxicity in mice, we designed and synthesized Axl/Mer inhibitors and Axl-selective inhibitors. We identified an Axl/Mer dual inhibitor 28a, which showed retinal toxicity at a dose of 100 mg/kg in mice. Subsequent derivatization of a pyridine derivative led to the discovery of a pyrimidine derivative, 33g, which selectively inhibited the activity of Axl over Mer without retinal toxicity at a dose of 100 mg/kg in mice. Additionally, the compound displayed in vivo anti-tumor effects without influencing body weight in a Ba/F3-Axl isogenic subcutaneous model.